Adapting a Psychosocial Intervention to reduce HIV risk among likely adolescent participants in HIV biomedical trials - Dietrich, Janan Janine (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015